Cyber terrorism : a guide for facility managers - Gustin, Joseph F., 1947- (Fairmont Press ; Marcel Dekker, 2004)
Addressing cyberterrorism and other terrorist activity including mailroom security, bomb threats, viruses, hackers and invasive programs, this book identifies known terrorists. It addresses the necessary steps needed for prevention of their attacks.